Mitochondrial Dysfunction and Oxidative Stress in Pediatric Diseases - Lotti, Federica; Perrone, Serafina; Geronzi, Ursula; Guidoni, Elisa; Carra, Federica; Belvisi, Elisa; Bazzini, Francesco; Buonocore, Giuseppe; Grosso, Salvatore; on behalf of the “Gruppo di Studio di Biochimica Clinica Neonatale della Società Italiana di Neonatologia” (Journal of Pediatric Biochemistry, 2016)
Oxidative stress is a distinctive sign in a long series of human diseases, including metabolic, neurologic, and cancer disorders. Several studies demonstrated that the toxic effects resulting from a redox imbalance take place even during infant age. Recent literature focused in particular on the role exerted by unpaired mitochondrial function in the pathogenesis of these diseases. Oxidative damage and mitochondrial dysfunction are cofactors in the pathogenesis of diabetes, as well as major contributors to its associated complications, primarily represented by cardiovascular disease. In epilepsy, mitochondrial failure is thought to be one of the possible mechanisms for seizure generation through a dysregulation in calcium homeostasis; moreover, the prolonged seizure-related neuronal excitation is able to trigger mitochondrial damage, proving the existence of interdependency between epileptic activity and mitochondrial dysfunction. Oxidative stress plays a pivotal role in carcinogenesis, and its intervention has been demonstrated in the pathogenesis of cancer-prone genetic diseases. The identification of specific molecular targets linked to altered mitochondrial function allows to select more rational and appropriate supportive treatments using antioxidants and mitochondrial nutrients as potential new therapeutic approaches.
Keywords: oxidative stress; diabetes mellitus; epilepsy; cancer; mitochondrial dysfunction; antioxidants